Aperture Crossing in Virtual Reality: Physical Fatigue Delays Response Time. Issue 4 (13th June 2022) - Snyder, Natalie A.; Cinelli, Michael E.
Abstract: Visual perception and cognitive (i.e., decision-making) abilities facilitate successful avoidance of obstacles in a person's environment. However, detrimental changes to cognition can occur after physical fatigue is induced by strenuous exercise. The purpose of the current study was to determine if obstacle avoidance behaviors reflect similar negative effects following physically fatiguing exercise. A virtual reality (VR) closing-gap aperture crossing task was completed by 13 recreationally active individuals to assess the effects of physical fatigue on passability judgements and response time. Participants approached closing apertures that moved at one of seven speeds while deciding to either pass through the closing aperture or stop. Participants completed four blocks of trials over a 7-day period (i.e., pre- and post-tests on the fatiguing day and control day). No significant differences for passability judgements were found across each of the blocks, but there was a significant reduction in response time on the post-test exercise day. Thus, physical fatigue increased the time required to make, and follow through on, a decision. The current findings suggest that processes requiring more cortical areas and processing (i.e., response time) may be more detrimentally affected by physically fatiguing exercise compared to dichotomous visuomotor tasks (i.e., passability judgements).